Determinants of Intrinsic Value in Plantation Companies: An Analysis of Palm Oil Productivity, Firm Size, and Financial Performance on Indonesia Stock Exchange: English - Rina Sitepu, Dewinta; Fachrudin, Khaira Amalia; Bulan Siregar, Narumondang (CV. ARGA FARMA, 2024)
The palm oil industry is a cornerstone of Indonesia’s economy, contributing significantly to GDP, exports, and employment. As the largest global palm oil producer, Indonesia supports a vast international market but faces challenges related to productivity and sustainability. This study investigates the influence of productivity, firm size, profitability, liquidity, and leverage on the intrinsic value of plantation companies listed on the Indonesia Stock Exchange (IDX) from 2018–2022. Employing a quantitative methodology, panel data regression analysis was applied to a sample of 14 companies, selected through purposive sampling, representing a focused yet representative subset of the population. Intrinsic value was calculated using the Free Cash Flow to Firm (FCFF) model under the Discounted Cash Flow (DCF) approach. The findings reveal that firm size significantly enhances intrinsic value, indicating that larger firms benefit from economies of scale and better access to financing. However, productivity, profitability, liquidity, and leverage, while positively correlated, show statistically insignificant effects, suggesting that external factors such as global commodity price volatility and inefficiencies in financial management may play a role. This study underscores the critical role of firm size in driving intrinsic value while calling for further exploration of external factors impacting the palm oil sector. The results offer valuable insights for investors and policymakers in fostering financial performance and sustainable industry growth.